2009
DOI: 10.1182/blood-2008-12-195883
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of NADPH oxidases in megakaryocytes and their role in polyploidy

Abstract: IntroductionMegakaryocytes (MKs) are platelet precursors in the bone marrow (BM) that undergo a complex maturation process called megakaryopoiesis. A hallmark of MK development occurs after their commitment to the MK lineage, in which MKs go through iterative rounds of endomitosis to become large polyploid cells. These cells can contain DNA content of up to and greater than 128N, with 2N being normal diploid DNA content. 1 The primary stimulus for progression of megakaryopoiesis is known to stem from thrombopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 55 publications
3
31
0
2
Order By: Relevance
“…In addition, supplementary analyses showed that DPI treatment was also hindering differentiation: (1) the compound prevented the increase in cell size ( Figure 3c) and acquisition of the megakaryocytic morphological features ( Figure 3d); (2) the increase in the megakaryocytic markers (CD41 and CD61) and the decrease in the erythrocytic marker GpA were partially inhibited by DPI (Figure 3e 21 This would imply that ROS production might also be involved in cell-cycle progression, thus being crucial for endomitosis. In this sense, while this paper was in preparation, a report appeared describing the potential role of NADPH oxidases in megakaryocyte polyploidisation, 22 in agreement with our results (Figure 3f). Under our experimental condition, DPI did not affect cell viability (Supplementary Figure 4c) or mitochondrial potential (Supplementary Figure 4d).…”
Section: Resultssupporting
confidence: 92%
“…In addition, supplementary analyses showed that DPI treatment was also hindering differentiation: (1) the compound prevented the increase in cell size ( Figure 3c) and acquisition of the megakaryocytic morphological features ( Figure 3d); (2) the increase in the megakaryocytic markers (CD41 and CD61) and the decrease in the erythrocytic marker GpA were partially inhibited by DPI (Figure 3e 21 This would imply that ROS production might also be involved in cell-cycle progression, thus being crucial for endomitosis. In this sense, while this paper was in preparation, a report appeared describing the potential role of NADPH oxidases in megakaryocyte polyploidisation, 22 in agreement with our results (Figure 3f). Under our experimental condition, DPI did not affect cell viability (Supplementary Figure 4c) or mitochondrial potential (Supplementary Figure 4d).…”
Section: Resultssupporting
confidence: 92%
“…Previous in vivo studies using cyclin E1, E2 double knock-out mouse model showed that cyclin E is necessary for MK polyploidy (31). Recently, we reported that up-regulation of cyclin E partially restores the ploidy levels in NADPH oxidase-inhibited MKs, further supporting a role for cyclin E as an inducer of polyploidy (47). Here, we show that TPO stimulation of MKs highly up-regulates cyclin E. This finding suggests a role for cyclin E in TPO-mediated MK polyploidization.…”
Section: Discussionsupporting
confidence: 76%
“…At the histologic level, we also observed more extensive P-selectin staining, indicative of platelet activation/aggregation, 34 and integrin ␣IIb, a specific marker of platelet activation, 30,35 in the small perialveolar pulmonary vessels in the ThCD59 RBC mice treated with ILY 140 FI than in the ThCD59 RBC mice treated with ILY 140 SI ( Figure 5 and supplemental Figure 3). Moreover, platelet aggregates and thrombi specifically occurred in the pulmonary microvasculature, but not the vasculatures of other tissues such as kidney, liver, and heart of ThCD59 RBC mice treated with ILY 140 FI ( Figure 5; supplemental Figure 4).…”
Section: Cause Of Sudden Death In Acute Hemolysismentioning
confidence: 79%
“…Lung, liver, kidney, and heart sections were processed and stained with an anti-P-selectin (C20; Santa Cruz Biotechnology), rabbit anti-integrin ␣IIb 30 (sc-15 328; Santa Cruz Biotechnology), or rabbit anti-von Willebrand factor (VWF) 26 (Dako) antibody, 1:50 dilution, followed by the goat avidin-biotin complex (ABC) staining system (sc-2023 or sc-2018; Santa Cruz Biotechnology). Heart sections were stained with mouse anti-hCD59 monoclonal antibody Bric 229 (International Blood Group Reference Laboratory) and fluorescein isothiocyanate-conjugated horse anti-mouse secondary antibody as previously described.…”
Section: Tissue Histologymentioning
confidence: 99%